3D food printing: A review of history, functionality and challenges in product development (Research, Society and Development, 2025)
3D food printing is an innovative technology with the potential to transform food manufacturing, enabling personalization and the creation of sustainable products. This study aims to review the application of 3D printing in food production, addressing scientific and technological advancements. Using techniques such as extrusion, inkjet printing, and selective laser sintering, it is possible to produce foods from proteins, carbohydrates, and lipids. These nutrients play a crucial role in the formulation of printed foods, influencing properties like texture, viscosity, and stability, directly impacting the final quality of the products. Despite numerous advantages, such as customization and waste reduction, significant challenges remain. Among the main obstacles are technical complexity, high equipment costs, and limited public acceptance due to a lack of awareness about the benefits of 3D printing. Additionally, issues related to food safety, process standardization, and scalability must be addressed for the technology to achieve widespread adoption. The extrusion technique has been widely used due to its flexibility in handling viscoelastic formulations. However, further exploration of other techniques for food production, such as stereolithography and selective laser sintering, is necessary to expand application possibilities, particularly in creating foods with complex geometries or specific nutritional properties. It concludes that, despite current limitations, 3D printing has the potential to revolutionize food production by enabling the creation of products that meet the nutritional and sensory demands of modern consumers.